GAIN-WEIGHTED TECHNIQUE FOR DIRECTLY MEASURING LOOP BANDWIDTH OF SPLIT-LOOP PHASE-LOCKED LOOP - Kenington, P; Edwards, D; Mcgeehan, J (1989)
A technique is described, for directly measuring the loop bandwidth of the recently proposed split-loop phase-locked receiver. This technique takes advantage of recent advances in laboratory test equipment, and is both rapid and straightforward. The characteristics produced permit the actual loop parameters to be determined, thus providing verification of the calculated performance.